Modeling an optimal supply chain management system in transport systems - N. H. Маmеdov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The purpose of the work is to develop universal logistics approaches to modeling the optimal supply chain management system in the conditions of a multimodal service center.Method. The methodological basis of the study is theoretical and experimental research in the field of creating an effective model of supply chain management in transport systems.Result. A process approach to the strategic management of supply chains for the logistics of transport systems has been formalized, taking into account the influence of a group of factors; developed a methodology for managing relationships with suppliers, taking into account their integration in supply chain management; rational parameters for evaluating the effectiveness of the logistics management system for logistics under given working conditions were determined; a methodology has been developed for managing supply chains of logistics in the conditions of operation of a multimodal service center based on the application of the theory of experiment planning.Conclusion. Optimization of supply chain management (Supply Chain Management, SCM) allows you to effectively plan, form, control and regulate material, financial, information flows throughout the entire life cycle of goods. The resulting regression equations are recommended to be used as a mechanism for analyzing the work with the selected supplier when organizing the optimal management of supply and procurement processes in the transport system in the conditions of operation of the multimodal service center of GRAND MOTORS LLC.